Study of Millimeter-Wave Rotational Spectra ofTrioxane in Ground, v(A), v1(E) = 1 and v2(E) = 1 States - Masoud Motamedi; Najmehalsadat Khademi (E-Journal of Chemistry)
The millimeter-wave rotational spectra of the ground and excited vibrational states v(A), v1 (E) =1 and v2 (E ) =1 of the oblate symmetric top molecule, (CH2O)3, have been analyzed again. The B0 = 5273.25747MHz, D J = 1.334547 kHz, D Jk = -2.0206 kHz, H J (-1.01 mHz), H JK (-3.80 mHz), and HKJ (4.1 mHz) have been determined for ground state. For non degenerate excited state, vA(1), the B = 5260.227723 MHz and D J and D JK were determined 1.27171 kHz and -1.8789 kHz respectively. The 1=±1 series have been assigned in two different excited states v1 (E) =1 and v2 (E) =1.Most of the parameters were determined with higher accuracy compare with before. For the v2 (E) =1 state the Cζ=-1940.54(11) MHz and q J = 0.0753 (97) kHz were determined for the first time.